The Relationship Between Nutrition-Physical Activity Behaviors of Autistic Children with Their Families and Children's Obesity Levels During Covid Pandemic. - GUNER U, Umran CEVİK; İrem, BİLKAY (Journal of Autism & Developmental Disorders, 2024)
The family has a key role in the obesity management of children with autism. This study examines the relationship between the nutrition-physical activity behaviors of autistic children with their families and children's obesity levels during covid-19 pandemic. The descriptive and cross-sectional study involved 80 parents of autistic children. A positive correlation was found between children's mean BMI values before and during the pandemic(p = 0.000). Family Nutrition and Physical Activity Scale(FNPAS) and Brief Autism Mealtime Behavior Inventory(BAMBI) score were 55.18 ± 7.86 and 31.76 ± 8.79, respectively. In addition, it was found that 32.5% of the children ate more than before the pandemic, 50.0% engaged in less physical activity, and 16.3% didn't do any physical activity. The study results suggesting the risk of obesity.